Zadania domowe w perspektywie uczniów na przykładzie przedmiotu geografia - Abramowicz, Dawid (Studia Edukacyjne, 2019)
Homework in school education is one of the most important challenges in the educational process. Considerations regarding homework and its efficiency result from various approaches in both academic and school environments. Despite various opinions, discussions and the results of research on education, and at the same time the lack of legal necessity to apply homework, they remain an integral part of the education process in most schools. The aim of the research was to recognize students’ opinions on homework. The study presents the results of research on the use of obligatory and non-obligatory home tasks in geography lessons. According to the students, the use of compulsory homework in a Geography lesson adversely affects their mobilization for learning outside of school. Students pay attention to the problem of a small amount of time that they could devote to the pursuit of their interests. In their opinion, the possibility to decide on the form of homework would significantly increase their motivation to learn.